Creating a space for place and multidimensional well-being: lessons learned from localizing the SDGs - Sterling, Eleanor J.; Pascua, Puaʻala; Sigouin, Amanda; Gazit, Nadav; Mandle, Lisa; Betley, Erin; Aini, John; Albert, Simon; Caillon, Sophie; Caselle, Jennifer E.; Cheng, Samantha H.; Claudet, Joachim; et al. (Sustainability science, 2020)
Achieving sustainable development globally requires multilevel and interdisciplinary efforts and perspectives. Global goals shape priorities and actions at multiple scales, creating cascading impacts realized at the local level through the direction of financial resources and implementation of programs intended to achieve progress towards these metrics. We explore ways to localize global goals to best support human well-being and environmental health by systematically comparing the UN Sustainable Development Goals (SDGs) with regionally-derived well-being dimensions that encompass components of social–ecological resilience across the Pacific Islands. Our research shows that, in the context of the Pacific, there are overlaps but also significant gaps between regional conceptions of well-being and the globally-derived SDGs. Some dimensions, related to human health and access to infrastructure and finances, are well represented in the SDGs. Other dimensions of high importance when localizing perspectives of well-being, such as those regarding connections between and across people and place and Indigenous and local knowledge, are not. Furthermore, internationally generated indicators may result in trade-offs and measurement challenges in local contexts. Creating space for place-based values in global sustainability planning aligns with international calls for transformational changes needed to achieve global goals. We identify challenges in applying SDG indicators at the local level and provide lessons learned to foster equitable and holistic approaches and outcomes for sustainability.